2010
DOI: 10.1007/s11655-010-0109-9
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effect of combined therapy with Jinlong Capsule (金龙胶囊) and transcatheter arterial chemoembolization on patients with primary hepatic carcinoma and its influence on serum osteopontin expression

Abstract: The short-term clinical efficacy and the quality of life of patients with PHC can be improved by combining JLC with TACE. The serum OPN levels in PHC patients can reflect the curative effect of treatment and the prognosis of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 5 publications
0
28
0
Order By: Relevance
“…Jinlong Capsule may enhance shortterm effect of TACE and improve QOL in patients with unresectable hepatocarcinoma [78] . Syndrome differentiation based TCM therapy could enhance short-term efficacy and reduce adverse effect of TACE, improve immune function and QOL in liver cancer patients [79] .…”
Section: Tcm In Combination With Tacementioning
confidence: 99%
“…Jinlong Capsule may enhance shortterm effect of TACE and improve QOL in patients with unresectable hepatocarcinoma [78] . Syndrome differentiation based TCM therapy could enhance short-term efficacy and reduce adverse effect of TACE, improve immune function and QOL in liver cancer patients [79] .…”
Section: Tcm In Combination With Tacementioning
confidence: 99%
“…Recent studies showed that OPN is involved in the tumorigenesis of breast cancer [17,18,19], hepatic carcinoma [20], gastric cancer [21]. The role of OPN in thyroid cancer received much attention in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…TCM can also alleviate the adverse reaction of combined chemotherapeutic agents and promote the recovery of liver function in patients [74,75]. Secondly, TCM can significantly inhibit liver tumor growth and angiogenesis [76,77], while restraining the progress of liver cancer [78,79]. Thirdly, TCM can promote the immune response and improve the QOL of the patient by protecting life functions [74,80], and then prolong survival of patients and improve the prognosis of patients with unrespectable HCC [70,[81][82][83].…”
Section: Combination Of Tcm and Interventional Therapy For Treatment mentioning
confidence: 99%